Deteksi dan Identifikasi Ditylenchus dipsaci dari Umbi Bawang Putih Impor - Elmi Muliya; Supramana Supramana; Giyanto Giyanto (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2018)
Detection and Identification of Ditylenchus dipsaci from Imported Garlic BulbsImportation rate of garlic (Allium sativum) increased significantly in Indonesia lately. This situation may lead to the introduction and spread of quarantine pests, one of them is bulbborne nematode Ditylenchus dipsaci. This research is aimed to detect and identify the presence of D. dipsaci on imported garlic bulb from China. Samples of garlic bulbs were taken from imported garlic through Tanjung Priok Sea Port, North Jakarta, within importation period from August to December 2017. Nematode extraction was performed by modified Baermann funnel method. Nematode identification was carried out based on the D. dipsaci key morphological characters and morphometry according to de Man formula. This nematode was successfully detected from 20% of garlic bulbs samples based on morphological characteristics, i.e. slender body shape, body length between 0.56 until 1 mm, well-defined stylet (10-13 mm in length), posterior valve between oesophagus and intestine is not overlapping, median bulb obvious with oval shape, and the tail was conoid with a pointed terminus. The findings of D. dipsaci is an important fact because these nematodes have the potential to cause damage to plants in the field.